Measuring Human, Physical and Structural Capital Efficiency Performance of Insurance Companies - Mohammad, Nourani; Chandran, V.G.R.; Kweh, Qian Long; Lu, Wen Min (Springer Verlag, 2018)
Based on the strategy perspective of intellectual capital, this paper proposes an integrated framework that is practical to estimate the human, physical, and structural capitals (intellectual capital) efficiency performance, at firm level. This paper uses a dynamic network data envelopment analysis model to estimate the intellectual capital efficiency at three levels in the insurance industry over the period of 2005–2012. Within the insurance industry, deficiencies occurred in the human and structural capital stages as opposed to the physical capital stage. A further investigation indicates that total investment is the major concern for the deficiencies. Moreover, the cluster analysis highlights the strengths and weaknesses of the insurers based on their inherently similar efficiencies. Malaysian insurance industry need to translate and promote the existing knowledge-based economy agenda lauded by the government to improve the intellectual capital efficiency, particularly at the human capital level.